Tofacitinib Regulates β‐Catenin Nuclear Translocation to Inhibit FLS Migration and Alleviate Clinical Symptoms of RA - Shuqi Fang; Tianjing Zhang; Ling Hu; Ruijin Liu; Leyi Jia; Menglin Bai; Jiale Dong; Yuchen Zhao; Han Wang; Lei Zhang; Tao Li; Youcai Deng; et al. (iNew Medicine, 2026)
ABSTRACT Objective Tofacitinib is a Janus kinase (JAK) inhibitor approved for the treatment of moderate‐to‐severe rheumatoid arthritis (RA). However, its synovium‐related molecular mechanisms, particularly its regulatory effect on fibroblast‐like synoviocyte (FLS) migration, remain incompletely understood. This study aimed to investigate whether tofacitinib inhibits RA‐FLS migration through the IL‐6/STAT3/β‐catenin axis and to evaluate its clinical effectiveness in a real‐world RA cohort. Methods Primary FLS were isolated from synovial tissues of patients with RA or osteoarthritis (OA). Transwell migration assays, Western blotting, immunofluorescence staining, imaging flow cytometry, and nuclear/cytoplasmic fractionation were performed to assess FLS migration, STAT3/β‐catenin pathway activation, and β‐catenin nuclear translocation. STAT3 knockdown and β‐catenin overexpression experiments were performed in MH7A cells. A collagen‐induced arthritis (CIA) mouse model was used for in vivo validation. Clinical data from 140 patients with RA receiving tofacitinib were analyzed. Results The expression and nuclear localization of p‐STAT3 and β‐catenin were increased in RA synovium compared with OA controls. IL‐6 promoted FLS migration and proliferation, accompanied by STAT3/β‐catenin activation and enhanced β‐catenin nuclear translocation. STAT3 knockdown reduced β‐catenin expression and inhibited MH7A cell migration, whereas β‐catenin overexpression partially reversed these effects. Tofacitinib suppressed IL‐6‐induced STAT3/β‐catenin activation, reduced β‐catenin nuclear translocation, and attenuated FLS migration. In CIA mice, tofacitinib decreased synovial p‐STAT3 and β‐catenin expression and alleviated joint pathology. Real‐world follow‐up showed improved ACR response rates, DAS28‐ESR, HAQ‐DI, ESR, hs‐CRP, hemoglobin levels, and red blood cell counts. Conclusion Tofacitinib may alleviate synovial inflammation and pathological FLS migration in RA by inhibiting STAT3/β‐catenin signaling, supporting its clinical effectiveness and mechanistic role in regulating RA synovial pathology.